Bacterial Dysbiosis and Translocation in Psoriasis Vulgaris - Visser, Maria J. E.; Kell, Douglas B.; Pretorius, Etheresia (Frontiers in Cellular and Infection Microbiology, 2019)
Psoriasis vulgaris is a chronic inflammatory skin condition, associated with both a physical and a psychological burden. Our understanding of the aetiology of this disease remains incomplete. Conventionally, psoriasis has been viewed as a condition that manifests solely in the skin. However, the systemic inflammatory nature of this disease has been confirmed by the presence of a wide array of dysregulated cytokines and inflammatory markers in the serum of these patients. Both dysregulated gut and skin microbiomes have been found in association with psoriasis. An evident association also exists between inflammatory bowel disease and this condition. Regarding the skin microbiome, changes have been observed in the relative abundance of Firmicutes, Actinobacteria and Proteobacteria. Additionally, Staphylococcus and Streptococcus spp. were detected more frequently in lesional skin. Alterations in the gut microbiome have been characterised by a decrease in the Bacteroidetes phylum and an increase in the Faecalibacterium genus. We suggest that dysbiosis of the skin and gut microbiota may contribute to psoriasis, by promoting the translocation of microbes from these sites into the bloodstream. Consistent with the Iron Dysregulation and Dormant Microbes hypothesis, these microorganisms are in a physiologically dormant state, but may be awakened periodically and shed their cell wall components, such as lipopolysaccharide and lipoteichoic acid. Both of these inflammagens may contribute significantly to maintaining a chronic inflammatory state in the host, such as is seen in individuals diagnosed with psoriasis.